Implementasi Stakeholder Engagement dalam Sustainable Development Studi Kasus Pada PT XYZ - Adinda Bentang Chaerunisa; Sylvia Veronica Siregar (Politeknik Ganesha Medan, 2023)
The Oil and Gas industry is an industry that is very close to the issue of business sustainability due to the impact of its operational activities. Therefore, sustainability reports are very important for oil and gas companies as an important channel in meeting the needs and expectations of stakeholders. However, PT XYZ as an oil and gas company still has not published a stand-alone sustainability report, and has not been registered in PROPER. Thus, this study aims to analyze the design of stakeholder engagement at PT XYZ, and identify material topics that will serve as the basis for PT XYZ's sustainability report. This research is identified as a single-case study. The data collection methods used are interviews and documentation studies. In this study, the level of stakeholder engagement is identified in more detail, as well as associated with material topics. This research is expected to help the management of PT XYZ in managing stakeholder engagement effectively, understanding priority issues, and publishing a stand-alone sustainability report that can meet the needs and expectations of all PT XYZ stakeholders. The results show that among the four stages of stakeholder engagement design, the monitoring stage is still not done optimally because it has not been applied to all stakeholders. Furthermore, there are 16 material topics in PT XYZ, and 4 out of 16 material topics become priority issues because these topics have the highest impact on PT XYZ stakeholders.